1990
DOI: 10.1111/j.1365-2141.1990.tb02596.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive quantitation of liver iron‐overload by magnetic resonance imaging

Abstract: A standard magnetic resonance imaging (MRI) system allowing spin echo times of 10 ms was used to quantitate liver iron concentration in nine healthy normal subjects and 13 patients with various grades of iron overload. Body iron status was estimated by measuring the serum ferritin concentration. In 11 subjects (two normal healthy controls, eight patients with HLA-related hereditary haemochromatosis and one patient with thalassaemia major) non-haem hepatic iron concentration was determined chemically in biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
2
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 9 publications
(7 reference statements)
2
96
2
3
Order By: Relevance
“…Localized regions of increased magnetic susceptibility selectively shorten T2 relaxation time by creating regions of magnetic field nonuniformity [9]. Recently, KALTWASSER et al [10] reported a strong correlation between T2 relaxation time and hepatic iron concentration measured in biopsy specimens and a moderate correlation with serum ferritin. Likewise, GOMORI et al [11] found a significant correlation between hepatic T2 relaxation time and iron concentration measured in surgical wedge samples from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Localized regions of increased magnetic susceptibility selectively shorten T2 relaxation time by creating regions of magnetic field nonuniformity [9]. Recently, KALTWASSER et al [10] reported a strong correlation between T2 relaxation time and hepatic iron concentration measured in biopsy specimens and a moderate correlation with serum ferritin. Likewise, GOMORI et al [11] found a significant correlation between hepatic T2 relaxation time and iron concentration measured in surgical wedge samples from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Localized MR spectroscopy measurements in the vicinity of the biopsy site have shown good correlation (r ϭ 0.95) with LIC up to 37.2 mg Fe/g dry tissue. 32 However, a limitation of localized spectroscopy measurements is the inability to measure or image the spatial variation in LIC.…”
Section: Liver Iron Heterogeneity and Rmentioning
confidence: 94%
“…Clinically useful estimates of the hepatic iron content have been obtained by a superconducting quantum interference device (SQUID) 5,6 and by magnetic resonance imaging (MRI). [7][8][9][10][11][12][13] Estimation of myocardial iron by the SQUID has so far not been reported, but a few studies have explored the use of MRI for this purpose. [14][15][16][17][18] Except for 2 studies, 14,18 all studies demonstrated a significant correlation between the applied myocardial MRI index and the serum ferritin concentration by heart-to-muscle signal intensity ratio (SIR) measurements obtained from spin-echo images, 15,17 by T2 relaxometry, 15,16 or by magnetization transfer ratio measurements.…”
Section: Introductionmentioning
confidence: 99%